Structural and electronic properties of manganese-doped Bi2Te3 epitaxial layers. (15th January 2015) - Růžička, J; Caha, O; Holý, V; Steiner, H; Volobuiev, V; Ney, A; Bauer, G; Duchoň, T; Veltruská, K; Khalakhan, I; Matolín, V; Schwier, E F; et al.
Abstract: We show that in manganese-doped topological insulator bismuth telluride layers, Mn atoms are incorporated predominantly as interstitials in the van der Waals gaps between the quintuple layers and not substitutionally on Bi sites within the quintuple layers. The structural properties of epitaxial layers with Mn concentration of up to 13% are studied by high-resolution x-ray diffraction, evidencing a shrinking of both the in-plane and out-of plane lattice parameters with increasing Mn content. Ferromagnetism sets in for Mn contents around 3% and the Curie temperatures rises up to 15 K for a Mn concentration of 9%. The easy magnetization axis is along the c -axis perpendicular to the (0001) epilayer plane. Angle-resolved photoemission spectroscopy reveals that the Fermi level is situated in the conduction band and no evidence for a gap opening at the topological surface state with the Dirac cone dispersion is found within the experimental resolution at temperatures close to the Curie temperature. From the detailed analysis of the extended x-ray absorption fine-structure experiments (EXAFS) performed at the Mn K -edge, we demonstrate that the Mn atoms occupy interstitial positions within the van der Waals gap and are surrounded octahedrally by Te atoms of the adjacent quintuple layers.